The Design and Development of Mobile Application Navigation: UUM Navigate Campus Companion (Journal of Digital System Development, 2024)
In recent years, the proliferation of mobile devices has revolutionised the accessibility and functionality of location-based applications, rendering traditional computer devices less effective for real-time location tracking and navigation. Recognising this shift, this paper presents the design and development of "UUM Navigate: Campus Companion," a mobile application specifically tailored for students at Universiti Utara Malaysia (UUM). The application is designed to assist new and lower-semester students in navigating the campus, accessing essential service facilities information, and find answers to frequently asked questions (FAQs) about UUM. The development process of UUM Navigate followed the ADDIE model, encompassing five key stages: Analysis, Design, Development, Implementation, and Evaluation. The evaluation phase was conducted in two parts: formative and summative assessments. Formative evaluation involves expert reviews to gather feedback for refining the application during its development. A summative evaluation was conducted post-development and aimed to collect 35 user responses through a survey distributed to UUM students via Google Forms. The survey assessed the application's usefulness, ease of use, and overall user satisfaction. The results indicate that despite the introduction of the application, many new and lower-semester students still need help locating classrooms and often need to be made aware of available campus services and facilities. However, most users provided positive feedback regarding the application's performance, highlighting its value as a practical tool for new students. The findings affirm the usefulness of the UUM Navigate: Campus Companion in enhancing campus navigation and accessibility for students, particularly those in their early semesters.